Disparities in cervical screening participation: a comparison of Russian, Somali and Kurdish immigrants with the general Finnish population - Esther E. Idehen; Päivikki Koponen; Tommi Härkänen; Mari Kangasniemi; Anna-Maija Pietilä; Tellervo Korhonen (BMC, 2018)
Abstract Background Cervical cancer is currently ranked as the fourth commonly diagnosed cancer in women globally. A higher incidence has been reported in low- and-middle-income countries, and the disease poses significant public health challenges. Evidence suggests that this disease is preventable by means of regular screening using the Papanicolaou (Pap) test. However, limited knowledge exists about disparities in cervical screening participation among immigrants compared with non-immigrants, in countries with universal cervical screening programmes. We aimed to examine disparities in cervical screening participation among women of Russian, Somali, and Kurdish, origin in Finland, comparing them with the general Finnish population (Finns). We controlled for differences in several socio-demographic and health-related variables as potential confounders. Methods We employed data from the Finnish Migrant Health and Well-being Study 2010-2012 and the National Health 2011 Survey. Data collection involved face-to-face interviews. Data on screening participation in the previous five years from women aged 29-60 were available from 537 immigrants (257 Russians, 113 Somalis, 167 Kurds) and from 436 Finns. For statistical analyses, we used multiple logistic regression. Results Age-adjusted screening participation rates were as follows: Russians 79% (95% CI 72.9-84.4), Somalis 41% (95% CI 31.4-50.1), and Kurds 64% (95% CI 57.2-70.8), compared with 94% (95% CI 91.4-95.9) among Finns. After additionally adjusting for socio-demographic and health-related confounders, all the immigrant groups showed a significantly lower likelihood of screening participation when compared with Finns. The Odds Ratios were as follows: Russians 0.32 (95% CI 0.18-0.58), Somalis 0.10 (95% CI 0.04-0.23), and Kurds 0.17 (95% CI 0.09-0.35). However, when additionally accounting for country of origin-confounder interactions, such differences were attenuated. Conclusions Our results indicate disparities in screening participation among these immigrants and a lower likelihood of screening participation compared with the general Finnish population. To improve equity in cervical cancer screening participation, appropriate culturally tailored intervention programmes for each immigrant group might be beneficial.